The Sources of Knowledge of the Economic and Social Value in Sport Industry Research: A Co-citation Analysis - Torres-Pruñonosa, Jose; Plaza-Navas, Miquel Angel; Díez-Martín, Francisco; Prado-Roman, Camilo (Frontiers in Psychology, 2020)
The aim of this paper is to map the intellectual structure of scholarship on economic and social value in the sport industry. Given that bibliometric techniques are specially appropriate to identify intellectual structures of a field of knowledge and complements traditional literature reviews, a co-citation bibliometric analysis has been applied. This kind of analysis identifies networks of interconnections. Therefore, we aim to detect both the most and the least active research areas in this field, as well as their sub-disciplinary composition. Whereas there is an abundant literature on sport efficiency and economic efficiency in the sport industry, our main conclusion is the identification of a literature gap in regard to social value in sport organisation, which is expected to be a research opportunity for scholars. This is in line with the lack of standardisation in the measurement for social value in sport organisations. In fact, such as it has been done over the last decades analysing other industries with contributions to stakeholders’ and multi-fiduciary theory of stakeholders, both the creation of social value indicators for sport entities and the empirical analysis of social efficiency in sport institutions, are identified and outlined as future areas of research. Therefore, this bibliometric analysis will contribute to determine the future challenges that this area of research will face in the following years so as to fill the literature gap identified.